PENGARUH PEMBERIAN KREDIT USAHA EKONOMI PRODUKTIF TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT - Jatmiko, Anang Rohmad; Fathur Rohman, Mohamad; M.Si, Mas'adah (eBA Journal: Journal Economics, Bussines and Accounting, 2018)
The purpose of this study was to determine the effect of micro-credit to the productive economy increase public revenues, to identify any obstacles in lending economically productive activities. The method used was a survey and interviews. Analysis of the data used statistical analysis. The results of his research are no significant influence of the credit to the improvement of people's income. As the amount of increase in public revenue that runs in line with the amount of credit, then increase the number of their loans to be more and more people will receive credit so that more and more people whose incomes rise. Obstacles encountered in lending is a discrepancy in lending, mistakes in lending, error target in lending to the target group, the competitor that lenders are the same, most people are reluctant to accept credit reasons cannot return, and society productive get credit easily from the savings and loan cooperatives that without using a complicated procedure with a high-interest rate.